Conceptualization of Best Practice Approach to Professional Supervision in Child Protection Services Within a Statutory Agency in Malaysia - Chan, Soak Fong; Azman, Azlinda; Jamir Singh, Paramjit Singh (Asian Social Work Journal, 2025)
The care, safety and protection of children is a shared responsibilitiy of the whole society. Government policies such as the National Child Protection Policy have emphasized the importance of collaboration among agencies as well as with the informal care system (families, neighbours and communities) to facilitate children are appropriately protected from maltreatment and its consequences. In recent times, there is an increasing awareness of the complexity of the jigsaw components of best practice in relation to child protection and the important roles of professionally trained social work child protection workers in addressing these complexities. One of the import provision to best practice in child protection is professional supervision. In relation to this, the understanding of the overall conceptualization of best practice approach to professional supervision in child protection services within a statutory agency in Malaysia is hence important. The paper discusses the concepts of supervision, child protection and best practice in child protection services. It recognises that social work child protection workers within the statutory child protection system in Malaysia, particularly frontline workers urgently require supported and valuing work environment, that encourages professional development and supervision to facilitate their provision of best practice child protection services.